2012
DOI: 10.3109/02770903.2012.669441
|View full text |Cite
|
Sign up to set email alerts
|

Working Toward a Sustainable System of Asthma Care: Development of the School-Based Preventive Asthma Care Technology (SB-PACT) Trial

Abstract: Objective We previously conducted the School Based Asthma Therapy trial to improve adherence to national asthma guidelines for urban children through directly observed administration of preventive asthma medications in school. The trial successfully improved outcomes among these children; however several factors limit its potential for dissemination. To enhance sustainability, we subsequently developed a new model of care using web-based guides for efficient communications and integration within school and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Although SAPs have demonstrated positive clinical outcomes, these programs encounter challenges related to sustainability and dissemination, including a lack of standardized outcome measures, an overreliance on outside organizations, and resource barriers . Furthermore, schools and PCPs often do not function together effectively in SAPs, with both groups acting independently without much coordination and communication .…”
mentioning
confidence: 99%
“…Although SAPs have demonstrated positive clinical outcomes, these programs encounter challenges related to sustainability and dissemination, including a lack of standardized outcome measures, an overreliance on outside organizations, and resource barriers . Furthermore, schools and PCPs often do not function together effectively in SAPs, with both groups acting independently without much coordination and communication .…”
mentioning
confidence: 99%
“…We found that many of the barriers in the original study were overcome with a web-based mechanism for asthma screening, control monitoring, report generation, and medication authorization. Although some challenges in implementation were encountered, 11 in general we found the system to be feasible and efficient. Caregivers, providers, and school health staff expressed general satisfaction with the program and the majority stated that this program should continue within the school district.…”
Section: Discussionmentioning
confidence: 93%
“…Further, the original study included an additional home-based smoke reduction component that was not included in the cost analysis or subsequent SBAT studies. 51 This decision was made based on our primary analysis that demonstrated that the improvement in asthma symptoms in the treatment group was independent of children' s cotinine level. 27,51 We did, however, control for family smoking status in all analyses.…”
Section: Discussionmentioning
confidence: 99%